2019
DOI: 10.21323/2414-438x-2019-4-3-24-31
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy as a Destabilizing Factor of Meat Quality Formation

Abstract: This review paper is devoted to myopathy of slaughter animals and poultry, and examines a relationship between fast growth of muscle tissue in hybrid pigs, broiler chickens and turkey, and high frequency of detection of spontaneous or idiopathic myopathies. The development of myopathy reduces consumer and technological properties of meat, and leads to emergence of different pathological conditions (PSE or RSE meat, «destructured meat», «white» or «green» meat, punctate hemorrhage, «wooden breast» and others).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(71 reference statements)
0
7
0
3
Order By: Relevance
“…This is confirmed by previous research by Bogucka et al [ 47 ], who also showed a significant beneficial effect adding a synbiotic to chickens’ diet had on the percentage of split fibers. Despite the inconclusive results of Semenova et al [ 58 ], they recommend the use of feed additives (selenium, vitamin E, flavonoids, etc.) in order to reduce the occurrence of pathological changes, which appears to be decisively linked with the quality of meat.…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed by previous research by Bogucka et al [ 47 ], who also showed a significant beneficial effect adding a synbiotic to chickens’ diet had on the percentage of split fibers. Despite the inconclusive results of Semenova et al [ 58 ], they recommend the use of feed additives (selenium, vitamin E, flavonoids, etc.) in order to reduce the occurrence of pathological changes, which appears to be decisively linked with the quality of meat.…”
Section: Resultsmentioning
confidence: 99%
“…A major factor for the occurrence of DPM is undoubtedly rearing conditions. It is well known that the live weight of broiler chickens and turkey increased by more than two times over the last 50 years mainly due to the size of pectoral muscles (Semenova et al, 2019). An increase in incidence of DPM is connected with the increase in growth rate and muscle size.…”
Section: Th E Main Risk Factors Associated With the Occurrence Of Dpmmentioning
confidence: 99%
“…The negative correlation between the quantity of muscle tissue in a carcass and pork quality is becoming more and more evident [1]. The genetic progress increased the burden on fast-growing slaughter animals, led to morphological and biochemical modifications of muscle tissue and, as a consequence, to deterioration of consumer properties of meat [2].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle tissue lesions, in which pathological changes in muscle fibers are observed ranging from degenerative changes to postmortem development of hypertonus giant fibers, are assigned to the main signs of myopathy (Greek: mys, my[os] muscle + pathos: suffering, disease) [2]. All animal species and even insects are prone to myopathy.…”
Section: Introductionmentioning
confidence: 99%